Maternal perception of fetal movements: Views, knowledge and practices of women and health providers in a low-resource setting - Katinka Weller; Natasha Housseine; Rashid S. Khamis; Tarek Meguid; G. Justus Hofmeyr; Joyce L. Browne; Marcus J. Rijken (Public Library of Science (PLoS), 2023)
The study assessed perception, knowledge, and practices regarding maternal perception of fetal movements (FMs) among women and their healthcare providers in a low-resource setting. Semi-structured interviews, questionnaires and focus group discussions were conducted with 45 Zanzibar women (18 antenatal, 28 postpartum) and 28 health providers at the maternity unit of Mnazi Mmoja Hospital, Zanzibar, Tanzania. Descriptive and thematic analyses were conducted to systematically extract subthemes within four main themes 1) knowledge/awareness, 2) behavior/practice, 3) barriers, and 4) ways to improve practice. Within the main themes it was found that 1) Women were instinctively aware of (ab)normal FM-patterns and healthcare providers had adequate knowledge about FMs. 2) Women often did not know how to monitor FMs or when to report concerns. There was inadequate assessment and management of (ab)normal FMs. 3) Barriers included the fact that women did not feel free to express concerns. Healthcare providers considered FM-awareness among women as low and unreliable. There was lack of staff, time and space for FM-education, and no protocol for FM-management. 4) Women and health providers recognised the need for education on assessment and management of (ab)normal FMs. In conclusion, women demonstrated adequate understanding of FMs and perceived abnormalities of these movements better than assumed by health providers. There is a need for more evidence on the effect of improving knowledge and awareness of FMs to construct evidence-based guidelines for low resource settings.